PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN PETA KONSEP PADA SISWA KELAS IV SD NEGERI 015 RAMBAH T.P 2014/2015 - Nurhayati Lubis (STKIP Rokania Pasir Pangaraian, 2018)
Learning improvement research has been carried out with the title Efforts to Improve Social Learning Outcomes Using Concept Maps for Students in Class IV Semester II SD N 015 to Increase 2014/2015 Academic Year. To find out the social studies learning outcomes in grade IV SD N 015 Spread the research conducted in March d. April 2014. The subjects of this study were 18th grade students as many as 18 people consisting of 8 men and 10 women. Parameters measured are student learning outcomes including absorptive capacity and learning completeness obtained from post test and Daily Test, student learning activities and teacher activities. Results of Daily Repetition Before Improvement with an average of 64.2 with sufficient categories, UH in the first cycle averaged 74.4 in the Good category, UH in cycle II averaged 80 with good categories. Completeness of student learning before improvement 9 (50%), 15th cycle I (83.3%), only achieved classical completeness in cycle II, namely 16 (88.9%). Student activity, reading textbooks, working on LKS containing concept maps, presentations and responding to presentation results, asking questions and answering questions. The activeness percentage of the first cycle was 83.3 in the Very Good category, in the second cycle it increased to 88.9 in the excellent category. Teacher activity also experienced an increase in cycle I on average 85 with excellent categories, cycle II on average 95 with excellent categories. From the results of the study it can be concluded that the use of concept map strategies can improve students' social studies learning outcomes in grade IV semester II SD N 015 reaching 2014/2015 academic year